2020
DOI: 10.1177/1042258719899427
|View full text |Cite
|
Sign up to set email alerts
|

Equity Crowdfunding: High-Quality or Low-Quality Entrepreneurs?

Abstract: Equity crowdfunding (ECF) has potential benefits that might be attractive to high-quality entrepreneurs, including fast access to a large pool of investors and obtaining feedback from the market. However, there are potential costs associated with ECF due to early public disclosure of entrepreneurial activities, communication costs with large pools of investors, and equity dilution that could discourage future equity investors; these costs suggest that ECF attracts low-quality entrepreneurs. In this paper, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 84 publications
3
56
0
Order By: Relevance
“…In addition, 40% of enterprises that failed to raise funds went bankrupt by the survey time; this was 2.9 times the proportion of enterprises that could raise funds and 7.2 times the proportion of enterprises that chose debt financing. Blaseg et al (2020) and Vismara (2019) also supported the last-resort hypothesis. They found that ECF initially attracted high-quality entrepreneurs, but the costs of information disclosure and communication with investors kept those entrepreneurs away.…”
Section: Characteristics Of Enterprises Implementing Ecfsupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, 40% of enterprises that failed to raise funds went bankrupt by the survey time; this was 2.9 times the proportion of enterprises that could raise funds and 7.2 times the proportion of enterprises that chose debt financing. Blaseg et al (2020) and Vismara (2019) also supported the last-resort hypothesis. They found that ECF initially attracted high-quality entrepreneurs, but the costs of information disclosure and communication with investors kept those entrepreneurs away.…”
Section: Characteristics Of Enterprises Implementing Ecfsupporting
confidence: 55%
“…Blaseg et al (2020) and Vismara (2019) also supported the last-resort hypothesis. They found that ECF initially attracted high-quality entrepreneurs, but the costs of information disclosure and communication with investors kept those entrepreneurs away.…”
Section: Prior Researchsupporting
confidence: 55%
See 1 more Smart Citation
“…We opine that this reversal is driven by a preference for signals from knowledgeable professionals (as opposed to mainstream consumers) in these high-risk product domains. This moderator variable may help reconcile the often polarized views regarding the value of crowdfunding identified in the marketing and innovation literature (e.g., Blaseg, Cumming, and Koetter 2020;Mollick and Kuppuswamy 2014).…”
Section: Theoretical Contributionsmentioning
confidence: 90%
“…If investors are not able to discriminate between good and bad crowdfunding campaigns, likely adverse selection dynamics may initiate, leading to the crowding-out of high-quality startups (Johan & Zhang, 2020). If so, equity crowdfunding may be relegated as the last resort, available for firms that have been discarded by all other sources of financing (Walthoff-Borm et al, 2018aBlaseg et al, 2021). Understanding under which conditions these dynamics are more or less likely to initiate becomes crucial to ensure the long-term feasibility of equity crowdfunding.…”
Section: Low-quality Projectsmentioning
confidence: 99%